The Production Scale of the Coconut Sugar Commodities in Purbalingga Post Covid-19 Pandemic - Arifin Agus; Priyono Rakhmat; Binardjo Goro; Cheong Chew Boon (E3S Web of Conferences)
Coconut sugar has become a leading commodity in Purbalingga Regency. It is a substitute product for granulated sugar with a low glycaemic index, so it is a product with high demand. This research aims to analyse (1) coconut sugar productivity and (2) coconut sugar production scale. The analysis methods include multiple regression analysis using the Cobb-Douglas function approach to analyse productivity and return to scale analysis to analyse production scale (CRS, IRS, or DRS). The research results show that (1) capital and coconut sap production have a positive effect on coconut sugar production, while the number of labours has no effect and (2) the scale of coconut sugar production shows decreasing return to scale (DRS). These findings are proof that the Covid-19 pandemic is still having a big impact on their business. Therefore, the local government must take a major role in supporting this leading industry, such as providing technical and financial assistance along with intensive mentoring so that their businesses return to normal.